Multidrug‐resistant Trichophyton mentagrophytes genotype VIII in an Iranian family with generalized dermatophytosis: report of four cases and review of literature. (13th October 2020) - Fattahi, Azam; Shirvani, Fariba; Ayatollahi, Azin; Rezaei‐Matehkolaei, Ali; Badali, Hamid; Lotfali, Ensieh; Ghasemi, Reza; Pourpak, Zahra; Firooz, Alireza
Abstract: Background: The global spread of terbinafine‐resistant Trichophyton mentagrophytes with point mutations in the squalene epoxidase ( SQLE ) gene is a big concern. Aim: The present study presents a series of unusual familial cases of generalized dermatophytosis caused by multidrug‐resistant T. mentagrophytes genotype VIII. Methods: Initially, the skin samples of each patient were taken and then subjected to direct microscopy and culture in Mycosel Agar. The molecular identification of Trichophyton species (spp.) was performed for all family members. In addition, the immunologic tests were requested, and an antifungal susceptibility test was carried out using the broth microdilution protocol based on the Clinical and Laboratory Standards Institute M38, third edition. The SQLE gene for a terbinafine‐resistant T. mentagrophytes genotype VIII was sequenced and confirmed its nucleotide sequence to KU242352 as a susceptible strain. Results: Based on the results of mycological examination and ITS rDNA sequencing, the etiologic agent was identified as T. mentagrophytes as a zoophilic dermatophyte. This species showed multiple drug resistance in vitro against terbinafine (minimum inhibitory concentration (MICs ≥8 µg/ml), itraconazole (MIC ≥4), and fluconazole (MIC ≥16). The SQLE gene of the isolate was subjected to sequencing for mutation, which showed a point mutation as TTC/TTA in the gene leading to Phe397Leu amino acid substitution in the enzyme. Only one of the family members responded to itraconazole and was cured after the long‐term use of itraconazole. Other family members were treated with oral voriconazole with no recurrence. Conclusion: The transmission of this resistant T. mentagrophytes to other countries due to globalization is a serious issue to be considered.